Entre l'Aigle, les Lys et la tiare Les relations des cardinaux d'Este avec le royaume de France (1530-1590) - Sénié, Jean (Premio Istituto Sangalli per la storia religiosa, 2021)
This research focuses on the d'Este cardinals' diplomatic and religious actions and on their role as mediators between Italy and France. The objective is to uncover the geopolitical foundations of their actions whilst highlighting the different scales thereof. The presence of Ippolito II and Luigi d'Este is studied both in terms of their material presence and their participation in the political stakes of the time. Finally, by examining their modus operandi on the international scene, this study argues that a Catholic identity is emerging which is not heterodox for which crossing the mountains leads to readjustments in manners of expressing and representing the Catholic faith.